2006
DOI: 10.1300/j010v43n04_06
|View full text |Cite
|
Sign up to set email alerts
|

Iraqi Gulf War Veteran Refugees in the U.S.

Abstract: Veterans of the Gulf War present various symptoms and maladies. Reports by governmental and private entities have yielded mixed results and have been fraught with criticisms of biased research design. The vast majority of these studies have focused on U.S. veterans, with a much smaller number focusing upon British veterans. Very few have examined Iraqi Gulf War veterans. Our study involves administering a health issues questionnaire to a sample of Iraqi Gulf War veteran refugees in the U.S. Results indicate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Initial comparisons revealed that the overall association between reported trauma and FSSs was more than twice as strong for males than females (male OR (95% CI) = 4.68 (2.28 – 9.59), n = 8; female OR (95% CI) = 2.13 (1.76 – 2.57), n = 37; X 2 = 4.31, df = 1, p = 0.038). However, as a conservative effort, three studies with outlier results [34, 36, 37] were excluded and the gender difference, although still present was no longer significant as a moderating variable (male OR (95% CI) = 3.29 (1.89 – 5.71), n = 6; female OR (95% CI) = 2.11 (1.74 – 2.55), n = 36; X 2 = 2.20, df = 1, p = 0.138).…”
Section: Resultsmentioning
confidence: 99%
“…Initial comparisons revealed that the overall association between reported trauma and FSSs was more than twice as strong for males than females (male OR (95% CI) = 4.68 (2.28 – 9.59), n = 8; female OR (95% CI) = 2.13 (1.76 – 2.57), n = 37; X 2 = 4.31, df = 1, p = 0.038). However, as a conservative effort, three studies with outlier results [34, 36, 37] were excluded and the gender difference, although still present was no longer significant as a moderating variable (male OR (95% CI) = 3.29 (1.89 – 5.71), n = 6; female OR (95% CI) = 2.11 (1.74 – 2.55), n = 36; X 2 = 2.20, df = 1, p = 0.138).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, Arab Americans (5.5%) had a lower estimate of major depression compared to Hispanics (7.0%), non‐Hispanic blacks, and whites (∼6.0%); however, this was not statistically significant. In previous studies, estimates for depressive symptoms or depression ranged from 13 to 49% (Amer & Hovey, ; Jamil et al., , , ; Jamil, Nassar‐McMillan, Salman, Tahar, & Jamil, ; Wrobel, Farrag, & Hymes, ). These estimates are higher than our estimate of 5.5%, which may be due to several factors.…”
Section: Discussionmentioning
confidence: 97%
“…These estimates are higher than our estimate of 5.5%, which may be due to several factors. First, some studies asked respondents to self‐report whether a physician has told them they had depression (Jamil et al., , , ), which is a question used in the Behavioral Risk Factor Surveillance System and has shown acceptable reliability and validity (Li, Ford, Zhao, Tsai, & Balluz, ). Perhaps the Arabic translation of this question does not capture depression or depressive symptoms as intended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Arab Americans, posttraumatic stress disorder (PTSD) is a common presenting issue in those seeking mental health services (Kamoo et al, ). Jamil, Nassar‐McMillan, Salman, Tahar, and Jamil () identified that, when compared with other Arab American immigrants, those that were a part of the fourth wave presented with the highest levels of anxiety, panic, and PTSD, all presenting symptomology that resulted from wartime trauma, torture, and the imprisonment faced before their immigration. Postmigration, after immigrants are no longer exposed to the imminent threat of death, they attempt to join their new society as a survivor.…”
Section: The Existential Anxietiesmentioning
confidence: 99%